Pengembangan Aplikasi e-Monev Pengadaan Barang Atau Jasa Badan Pengawasan Keuangan dan Pembangunan - Yuda, Afri (INFORMATIKA SAINS TEKNOLOGI, 2025)
The Procurement of Goods and Services (PBJ) within BPKP is a vital component in supporting transparent, efficient, and accountable national financial management. However, the Procurement Governance Index (ITKP) score in 2022, which stood at only 48.33, indicates the low quality of procurement governance, particularly in the area of monitoring and evaluation (monev), which has been conducted manually, in a decentralized manner, and requires a significant amount of time. This study aims to develop the e-Monev PBJ information system as a digital solution to support electronic, real-time, and integrated monitoring and evaluation processes across units. The system is designed to be user-friendly for different user roles, including decision-makers, procurement officials, and administrators. Key features developed in the system include secure login, a monitoring dashboard, user management (adding users, setting roles and access permissions), human resource management (employee data, job history, and certifications), as well as account management features such as profile editing, password changes, and user activity tracking. Keywords: PBJ, BPKP, Monev, Human Resource